ARTIFICIAL SEED PRODUCTION IN POINTED GOURD (TRICHOSANTHES DIOICA ROXB.) (Bangladesh Journal of Plant Breeding and Genetics, 2008)
Encapsulation of nodal segments was successfully developed for pointed gourd towards the formation of artificial seed with sodium alginate. Encapsulated nodal segments (artificial seed) were cultured in MS basal medium containing different concentrations and combinations of BAP and NAA to induce germination and shoot proliferation. Highest (95%) shoot formation was obtained in MS + 1.0 mg/l BAP followed by MS + 0.5 mg/l BAP. The encapsulated nodal segments also regenerated in vitro on different substrates. Frequency of plantlet formation was low on these substrates compared to plantlet development on MS media. Among these substrates, the percentage of plantlet formation was better on moist cotton (42%) followed by filter paper (35%). The hardened plants were transferred successfully to soil in the earthen pots. The protocol for encapsulating the nodal segments for the production of artificial seeds and their subsequent regeneration is a new area of research to develop in vitro conservation strategies for pointed gourd.DOI: http://dx.doi.org/10.3329/bjpbg.v21i1.17044